2018
DOI: 10.4103/ajts.ajts_4_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of irregular red cell antibody in healthy blood donors attending a tertiary care hospital in North India

Abstract: BACKGROUND:Alloantibodies may be detected in blood donors who have either been transfused previously or female donors with previous obstetric events. These antibodies can occasionally cause severe transfusion reaction, if a large amount of plasma or whole blood is transfused, as in massive transfusions and pediatric patients.AIMS:The present study aims to assess the prevalence of red cell antibodies in healthy blood donors at a tertiary care hospital-based blood bank in India.MATERIALS AND METHODS:A total of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
(24 reference statements)
2
13
0
Order By: Relevance
“…The higher rate of alloimmunization in females could be attributed to antigenic exposure during pregnancies. Other studies on healthy blood donors showed frequency of alloimmunization from 0.05 to 4.0 per cent 4 5 6 7 8 9 10 11 . In our study, most frequent alloantibodies identified were of MNS blood group system.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The higher rate of alloimmunization in females could be attributed to antigenic exposure during pregnancies. Other studies on healthy blood donors showed frequency of alloimmunization from 0.05 to 4.0 per cent 4 5 6 7 8 9 10 11 . In our study, most frequent alloantibodies identified were of MNS blood group system.…”
Section: Discussionmentioning
confidence: 91%
“…The prevalence of red cell alloantibodies varies in males and females (multiple pregnancies) and individuals with past history of transfusion and/or transplant. Red cell alloantibodies have been found in up to four per cent of blood donors 4 5 6 7 8 9 10 11 . Among patient populations, the prevalence of alloantibodies has been reported to be 2-9 per cent in multitransfused patients and 9-40 per cent in sickle cell anaemia and thalassaemia patients 12 13 14 .…”
mentioning
confidence: 99%
“…found these frequencies to be 2.1% and 1.31%, respectively. [ 9 10 ] The prevalence of anti-Le b among our donor population was found to be 0.13%.…”
Section: Discussionmentioning
confidence: 92%
“…As it is reminded in the monoclonal typing reagent insert accompanying the anti-M anti-sera, unexpected results may occur from very rare types of antigens. This warning was noted in one of the anti-M reagents we used (10). Some common monoclonal anti-M clones (e.g.2514E6 and M-11H2) extensively cross-react with the low prevalence He antigen (Henshaw, MNS6) (11).…”
Section: Discussionmentioning
confidence: 99%
“…Some common monoclonal anti-M clones (e.g.2514E6 and M-11H2) extensively cross-react with the low prevalence He antigen (Henshaw, MNS6) (11). Most anti-M reagents detect as well as He (Henschaw) which generally is found in 2.3 percent of the central African population (10). It is produced by DNA exchanging between the glycophorin A (GPA) and glycophorin B (GPB) genes, which are located close together on chromosome 4.…”
Section: Discussionmentioning
confidence: 99%